1985
DOI: 10.3758/bf03329765
|View full text |Cite
|
Sign up to set email alerts
|

Reading computer-presented text

Abstract: This experiment compared self-paced reading time and comprehension for subjects who read both paper-and computer-displayed passages. Reading time was longer and comprehension was less accurate for computer presentation than for paper presentation, but only when subjects were tested on the computer-presented texts first. These data raise the possibility that the processes involved in reading video text may not be comparable to traditional reading, especially without extensive practice on a given task. It is sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 6 publications
1
15
0
3
Order By: Relevance
“…However, many users, particularly older adult computer learners, cannot get used to operating a computer with a mouse or keyboard device, while others have trouble reading and remembering information presented on a computer screen. A previous study has found that comprehension was worse and reading was slower when reading from a computer screen compared with printed text (Belmore, 1985). This finding, however, was attributed to the subjects' lack of familiarity with computers and reading from screens.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, many users, particularly older adult computer learners, cannot get used to operating a computer with a mouse or keyboard device, while others have trouble reading and remembering information presented on a computer screen. A previous study has found that comprehension was worse and reading was slower when reading from a computer screen compared with printed text (Belmore, 1985). This finding, however, was attributed to the subjects' lack of familiarity with computers and reading from screens.…”
Section: Introductionmentioning
confidence: 56%
“…Regarding comprehension differences between print and screen reading, some earlier research found that comprehension was worse when reading from screen compared with print (e.g. Belmore, 1985;Gould et al, 1987). However, some studies reported no significant differences between levels of comprehension for screen and print presentations (e.g.…”
Section: Discussionmentioning
confidence: 88%
“…Such studies range from investigations of peripheral aspects of processing such as eye fixations (Rayner, 1978) to more central measures of processing such as presentation of text (Belmore, 1985). In previous research comparing text presented on the microcomputer with that presented on the printed page, differences in subjects' responses have been found.…”
Section: Computer Presentation Of Text Versus the Printed Pagementioning
confidence: 99%
“…The former refers to the inferior quality of material presented on-screen, due to which the acquisition of information proceeds more slowly compared to paper presentation (e.g. Belmore, 1985;Gray, 1991). Under circumstances of a strictly limited schedule to complete the assignment, it is not surprising that conditions leading to greater time consumption in task completion will induce performance deterioration in a test of maximal performance.…”
Section: Problem Statementsmentioning
confidence: 99%
“…As early as 1985, Belmore warned that text presentation on video display terminals [VDTs] was of a lower quality than text presentation on paper, leading to a poorer understanding of the material (Belmore, 1985). Furthermore, in a comparison between information searches on either paper or VDTs, the latter was shown to lead to a slower reading speed (Gray, 1991).…”
Section: Problem Statementsmentioning
confidence: 99%